OBLIGATORY COMMISSIONS AND CONSULTATIVE BODIES IN LEGISLATIVE BODIES OF TERRITORIAL SELF-GOVERNMENT UNITS IN POLAND AND TERRITORIAL COMMUNITIES IN FRANCE – DIRECTIONS OF CHANGES - Augustyniak, Monika (Review of European and Comparative Law, 2018)
The value of consultative democracy can not be overestimated, especially considering the local and supra-local administration gradually bringing the resident closer to self-government communities. Therefore, this issue is important and still requires improvement in the area of mutual relations between self-government authorities and residents of communes, districts/departments, voivodeships/regions. The search for common relations in participating in the management of the self-government community is a current challenge facing the territorial self-government in both legal orders. The comparative perspective in the scope of the functioning of commissions and consultative bodies of an obligatory nature is aimed at getting acquainted with the consultative administration in the territorial self-government in both legal orders and proposing directions of changes to Polish legal regulations in this area to improve the consultative dialogue and its normative tools.